The collection of Oriental art at the Vilnius Museum of Antiquities in 1862–1865 - Būčys, Žygintas (Acta Orientalia Vilnensia, 2010)
Vilnius UniversityThe present article provides a discussion about the collection of Oriental art acquired from Kronstadt residents in 1862 and exhibited at the Vilnius Museum of Antiquities. This was the first public collection of its kind in Lithuania. For this reason, the article is devoted to an analysis of the meanings and provisions that the Lithuanian scholarly community sought to impart to the exhibits of this collection as well as how they were perceived by the society at the time. A detailed discussion about the content of the collection, its attribution and donors is provided.